SIMULASI PROSES AKUISISI DAN TRACKING PADA SISTEM PENERIMA SPEKTRAL TERSEBAR HYBRID DIRECT-SEQUENCE/FREQUENCY-HOPPED - Rahmiati, Pauline
The subject presented in this thesis is the receiver of the spread spectrum telecommunication system. The use of spread spectrum telecommunication system has been rapidly growing. This system has many advantages such as multiaccess capability and jamming resistance. Whereas conventional receivers apply some filtering after despreading to recover the transmitted data, here a Discrete Fourier Transform (DFT) is applied. The DFT play a key role in both data detection and synchronization scheme (which can be split into two parts: acquisition and tracking). There are several spread spectrum techniques. The directsequence spread spectrum technique has a large processing gain but suffers from near-far effect The frequency-hopped spread spectrum is more resistant to the near-far effect, but the hardware is more complex. To retain the advantages of both DS and FH techniques while canceling their shortcomings, the hybrid DS/FH spread spectrum system is selected.